Leadership In The Public Servant As A Strategy To Improve The Quality Of Service In A Peruvian Municipality - Ganoza Ubillus, Lucila Maria (2024)
The current problem of the quality of service of our state entities is questioned by the way in which civil servants provide care, in this situation, it is necessary to make profound changes that contribute to achieving an efficient and effective state that seeks the continuous improvement of the quality of life of the citizen, and reduce existing gaps. The objective of this research is to propose a Server Leadership Program to improve the quality of service in a local government - Lambayeque Region - 2023, with a methodology of quantitative approach, applied type, non-experimental, descriptive-exploratory, cross-sectional and purposeful design, using the survey technique, validated by 5 experts, with a reliability of Cronbach's alpha of 0.933 for server leadership and 0.944 for service quality, the instrument was applied to a census sample of 100 public servants a local government of the Lambayeque Region, in the analysis of the results showed that both variables are at a medium level, the quality of service with 53% and the server leadership with 69%, likewise it was determined that the dimensions of the server leadership that provide guidance for the development of a program to improve the quality of service are empowerment, accountability, personal acceptance, authenticity and humility.